Comparison of inpatients who were readmitted within 28 days of discharge with those not readmitted: an audit at an Australian private psychiatric hospital. (April 2021) - Hope, Judith; Keks, Nicholas A; Pring, William; Adamopoulos, Voula; Toffler, David; Macfarlane, Stephen; Van Sebille, Debbie
Objective: To compare inpatients who had been readmitted within 28 days of discharge with patients not readmitted within the same period in a private psychiatric hospital. Method: Of 118 readmissions within 28 days in 2017 (7% of admissions), 50 were randomly selected and matched by age and gender with control patients who had not been readmitted within 28 days. Differences in demographics, diagnosis, length of stay and number of admissions in the previous 12 months were examined. Results: Readmitted cases were 64% female, were aged 49.8 ± 18.2 years (range 19–89), 40% were in relationships and 24% were receiving disability support. Most patients were suffering an episode of depression. Cases had higher rates of multiple psychiatric diagnoses ( p < .001) and physical disorders ( p < .05). There were no significant differences between cases and controls on psychiatric diagnoses. Cases had a longer length of stay in their previous admission ( p < .01) and a higher number of admissions in the preceding 12 months ( p < .05) compared to controls. Conclusion: This study indicates that inpatients readmitted within 28 days of discharge were more likely to have multiple diagnoses, physical co-morbidity and relapsing conditions than patients who were not readmitted.